Immunogenicity and Safety of a Third COVID-19 BNT162b2 mRNA Vaccine Dose in 5- to 11-Year Olds. Issue 4 (16th March 2023) - Simões, Eric A F; Klein, Nicola P; Sabharwal, Charu; Gurtman, Alejandra; Kitchin, Nicholas; Ukkonen, Benita; Korbal, Piotr; Zou, Jing; Xie, Xuping; Sarwar, Uzma N; Xu, Xia; Lockhart, Stephen; et al.
Abstract: In this ongoing study, substantially increased ancestral SARS-CoV-2 neutralizing responses were observed 1 month after a third 10-µg BNT162b2 dose given to 5 to 11-year olds versus neutralizing responses post-dose 2. After dose 3, increased neutralizing responses against Omicron BA.1 and BA.4/BA.5 strains were also observed. The safety/tolerability profile was acceptable. (NCT04816643) Abstract : A third BNT162b2 10-µg vaccine dose administered approximately 6 months after the second dose to 5- to 11-year olds increased neutralizing titers, including against Omicron BA.1 and BA.4/BA.5 strains. The safety and tolerability profile of the third BNT162b2 10-µg dose was acceptable.